Maternal counseling for preterm deliveries, assessing an effective method of counseling: A randomized trial - Shaaista Budhani; Mopelola Akintorin; Kenneth Soyemi; Louis Fogg; Mary Arlandson; Rajeev Kumar (PLoS ONE, 2025)
Objective To assess the acquired knowledge of mothers about prematurity outcomes when employing two distinct approaches to prenatal counseling among those experiencing preterm labor. A secondary aim was to assess the anxiety levels of trial subjects after the antenatal consultation. Study design Ninety-two pregnant women admitted between 23 and 34 weeks of gestation with threatened preterm labor were randomized in to two groups to receive either verbal counseling (Group 1) or verbal counseling supplemented with written and pictorial information (Group 2). Mothers completed a validated anxiety inventory and demographic questionnaire before counseling and an anxiety inventory and knowledge questionnaire after the counseling. There was a minimum two-hour gap between the counseling and completion of the questionnaire. Results Of the 92 women who completed the knowledge questionnaire, 45 (49%) were in Group 1 and 47(51%) in Group 2. Forty-three participants in group 1 and 45 participants in group 2 had their pre and post anxiety scores analyzed. There was a trend of increased recall rates in group 2 for short-term problems, long-term problems, intervention, and incidence rates, but it did not reach statistically significant level. There was an overall decrease in State Trait Anxiety Inventory (STAI) scores of participants after counseling (p = 0.002) but no statistically difference in change of STAI scores between the two groups (p = 0.981). Conclusion Based on the results of our study, regardless of the method of counseling there was no difference in knowledge assessment and comprehension of information. However, there was an overall decrease in anxiety level of mothers following any type of counseling. Trial registration ClinicalTrials.gov NCT02707237